Evaluation of Employee Work Posture for Facebook Account Creator with ROSA Approach at PT. Click Media - Windy Yuliani Putri Kaha; Moh. Dian Kurniawan (Indonesian Vocational Research Journal, 2021)
PT. Click Media is a service company in Lamongan that is engaged in web marketing to marketadvertising products to social media and websites. Employees of the Facebook Account Creator Sectionwork 8 hours per day with a working posture continuously dealing with computers. These conditionsmake complaints in the skeletal muscles or better known as musculoskeletal disorders. In the initialinterview conducted with the Nordic Body Map (NBM) questionnaire, the results showed that thehighest complaints were on the back of 81.8%, 54.5% of the upper neck, right hand, right wrist and 50%on the right shoulder. The method in this study is the Rapid Office Assessment (ROSA), which is anexclusive approach to office ergonomics to assess the level of work risk for computer users. The purposeof the study was to determine the level of occupational risk, the causes of musculoskeletal disorders,and recommendations for improvement. The results of the study were 50% of the 12 employees at riskwith a final score of 7 ROSA as many as 1 employee and a final score of 6 as many as 5 people. The causeof the problem occurs in the work facilities on non-adjustable chairs, the absence of armrests and roughsurfaces, non-adjustable backrests, the position of the monitor used by employees when working is verylow. And also the lack of awareness of employees of PT. Click Media in using the work tool creates anaccumulation of risk value. Recommendations for improvement are the renewal of work facilities suchas chairs that can be adjusted in height, have armrests and have a smooth surface, adjustable backrests,and monitors that are adjustable according to the employee's work position and socialization ofergonomic practices while working.